Protocol to image, segment, and quantify cortical contractions in maturing mouse oocytes - Gaëlle Letort; Elvira Nikalayevich (STAR Protocols)
Summary: Mouse oocytes devoid of branched actin display prolonged cortical contractions during the first meiotic division. Here, we present a protocol to collect fully grown oocytes in prophase I arrest and record their contractions during the first meiotic division through time-lapse imaging in transillumination, without additional labeling. We then explain how to set up the pipeline to segment the oocyte outline with an ImageJ plugin Oocytor and to measure cortical fluctuations with the help of an ImageJ plugin Radioak.For complete details on the use and execution of this protocol, please refer to Nikalayevich et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.